Legal and Administrative Analysis of Ombudsman’s Role in Resolving Public Service Maladministration in Indonesia - Jaka Maulana; Heru Wahyudi; Angga Rosidin (IHSA Institute, 2026)
Public service maladministration remains a significant challenge in Indonesia because it undermines citizens’ rights, weakens administrative justice, and reduces accountability in public service governance. This study aims to analyze the legal and administrative role of the Ombudsman of the Republic of Indonesia in resolving public service maladministration. The research employs a normative juridical approach complemented by qualitative administrative document analysis, using statutory regulations, scholarly literature, and institutional documents related to the Ombudsman’s authority, complaint-handling mechanisms, and institutional effectiveness. The findings show that the Ombudsman holds a strategic position as an independent external oversight institution with authority to receive complaints, examine allegations of maladministration, conduct investigations, facilitate corrective actions, and issue recommendations. Administratively, the Ombudsman functions as a complaint-resolution mechanism, an accountability forum, and a preventive institution for improving public service governance. However, its effectiveness is constrained by uneven compliance with recommendations, limited coercive enforcement, incomplete regulatory support for certain remedies, restricted institutional capacity, and variations in bureaucratic responsiveness. This study concludes that the effectiveness of the Ombudsman in resolving maladministration depends on the interaction between legal authority, administrative capacity, institutional compliance, and sustainable follow-up mechanisms